2015
DOI: 10.18805/lr.v38i5.5934
|View full text |Cite
|
Sign up to set email alerts
|

Stability of fenugreek (<italic>Trigonella foenum-graecum</italic> L.) genotypes for terminal heat and water stress

Abstract: Thirty genotypes of fenugreek (<italic>Trigonella foenum-graecum</italic> L.) were evaluated over four environments in randomized block design with 3 replications to estimate stability parameters of seed yield and its important component traits. The environments were created by changing the dates of sowing and irrigation levels. The genotypes interacted with the environments significantly indicating non linear response of genotypes to environments. Simple correlations between seed yield and other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…There is not any breeding background for this crop in Iran and local landraces are commonly used by farmers 4 . Due to the special geographical and climatic conditions of Iran, the occurrence of environmental stresses would be quite inevitable, so the identification of stress-tolerant plants with high yield potential or the use of various stimulants to improve plants tolerance, especially medicinal plants, seems necessary 5 .…”
Section: Introductionmentioning
confidence: 99%
“…There is not any breeding background for this crop in Iran and local landraces are commonly used by farmers 4 . Due to the special geographical and climatic conditions of Iran, the occurrence of environmental stresses would be quite inevitable, so the identification of stress-tolerant plants with high yield potential or the use of various stimulants to improve plants tolerance, especially medicinal plants, seems necessary 5 .…”
Section: Introductionmentioning
confidence: 99%
“…There is not any breeding background for this crop in Iran and local landraces are commonly using by farmers 48 . Due to the special geographical and climatic conditions of Iran, the occurrence of environmental stresses would be quite inevitable, so the identi cation of stress-tolerant plants with high yield potential or the use of various stimulants with the aim of improving plants tolerance, especially medicinal plants, seems necessary 35 . During the growing season, the fenugreek plant requires relatively cool and mild weather, so that temperatures above 35°C, especially at the beginning before the owering stage, damage this plant 43,42 .…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of photosynthesis function, denaturation of proteins and generation of heat shock proteins, decomposition of enzymes, reactive oxygen species accumulation, and disruption of plant cell walls are primary and vital damages caused by the high-temperature stress 45 . In previous studies, the adverse effects of hightemperature stress on the quality and quantity of fenugreek were well established, although biotic and abiotic stresses have effectively increased the content of some important secondary metabolites, such as diosgenin and trigonelline in fenugreek 23,43,35,19,36 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are defined phases in the life cycle of an annual crop like fenugreek namely vegetative (between seedling emergence and floral initiation), reproductive (between floral initiation and flowering) and grain filling (between anthesis and physiological maturity). The genotypes-environment interaction study was conducted by Meena et al (2015) showing the significantly non linear response of genotypes to environments. Simple correlations between seed yield and other traits indicated that pods per plant and the test weight are the two important component traits.…”
Section: Introductionmentioning
confidence: 99%